The Netherlands as a winter refuge for Light-bellied Brent Geese Branta bernicla hrota - Koffijberg, Kees; van Winden, Erik; Clausen, Preben (Wildfowl, 2013)
From 1978/79 onwards, eleven influxes of East Atlantic Light-bellied Brent GeeseÂ Branta bernicla hrota were recorded in the Netherlands, to the south of their regularÂ wintering areas in northern Denmark and northeast England. During most influxes,Â c. 3â€“6% of the total population occurred in the Netherlands, but large influxes inÂ 1995/96 and 2010/11 involved as many as 800â€“907 individuals, i.e. 18% and 11% ofÂ the flyway population respectively. Core wintering sites within the Netherlands wereÂ in the southwest Wadden Sea, in the northern part of Noord-Holland and in theÂ Delta area in the southwest of the country. The first two of these areas are thoughtÂ to have been more regular wintering areas for Light-bellied Brent Geese in the firstÂ part of the 20th century, although good documentation on numbers is lacking. TheÂ highest number recorded at a single site was 245 birds in Polder Kimswerd/Eendracht, Friesland, in December 2010. The distribution pattern was similar duringÂ all influxes, indicating traditional site use by the wintering flocks. Winters with peakÂ numbers in the Netherlands show a significant, negative correlation with averageÂ daily temperatures at the Danish wintering sites. During prolonged and/or heavyÂ cold spells, feeding conditions in Denmark deteriorate due to ice- or snow cover,Â making both aquatic and agricultural food resources unavailable and forcing birds toÂ depart; this was confirmed by count data from Denmark. In 1995/96, phenologicalÂ patterns and sightings of marked birds also indicated an influx from birds from theÂ wintering site at Lindisfarne in the UK, but this could not be confirmed for moreÂ recent winters. Sightings of marked birds showed that at least some birds (eight outÂ of 34 observed individuals) were involved in successive influxes; in non-influx yearsÂ they were seen regularly at wintering sites further up the flyway as well as on breedingÂ sites at Svalbard. The regular patterns of influxes, the traditional use of particularÂ sites during influx years and repeated observations of the same individuals at theseÂ sites (which may transfer knowledge of alternative wintering sites in the Netherlands to their offspring, indicated by ringed birds being seen with their goslings) illustrates that the Netherlands should be considered as a regular hard weather winter refuge for the sub-species. Appropriate measures therefore should be taken to include these sites within the national Natura 2000 network.